2021
DOI: 10.3389/fvets.2021.771573
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term Altrenogest Treatment Post-weaning Followed by Superovulation Reduces Pregnancy Rates and Embryo Production Efficiency in Multiparous Sows

Abstract: Although embryo transfer (ET) is a biotechnology ready for the swine industry, there are factors to be solved, the availability of embryo donors as one. Multiparous sows as donors ought to be considered since weaning is a natural and efficient method for estrus synchronization. In addition, superovulation treatments at weaning are effective in increasing the efficiency of donor embryo production. However, ET programs typically require more donors than those available from a single weaning, imposing grouping se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 53 publications
1
5
1
Order By: Relevance
“…Recent studies described that altrenogest administration in combination with gonadotropins had negative impacts on fertility and embryo viability for multiparous sows (Gonzalez-Ramiro et al, 2021.…”
Section: Induc Tion and Syn Chroniz Ation Of Ov Ul Ati On In Sowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies described that altrenogest administration in combination with gonadotropins had negative impacts on fertility and embryo viability for multiparous sows (Gonzalez-Ramiro et al, 2021.…”
Section: Induc Tion and Syn Chroniz Ation Of Ov Ul Ati On In Sowsmentioning
confidence: 99%
“…Altrenogest also acts at genetic level by downregulation of CYP17A1 mRNA in the prepubertal theca layer and PGF2 alpha synthase expression in the granulosa and theca layer of mature gilts. Recent studies described that altrenogest administration in combination with gonadotropins had negative impacts on fertility and embryo viability for multiparous sows (Gonzalez‐Ramiro et al, 2021, 2022).…”
Section: Induction and Synchronization Of Ovulation In Sowsmentioning
confidence: 99%
“…However, the situation becomes very different when superovulation is induced after the St-ALT treatment. Recently, we have shown that St-ALT administration before superovulation was efficient in delaying postweaning estrus and increasing the ovulation rates in weaned sows, but the treatments decreased fertilization, pregnancy, and embryo production rates compared to ALT-untreated, superovulated sows [13,14]. The poor results achieved after the combined use of St-ALT and superovulation treatments were mainly due to the increased proportions of immature oocytes and degenerated embryos compared to those obtained in ALT-untreated, superovulated sows and sows with natural estrus after weaning.…”
Section: Introductionmentioning
confidence: 96%
“…It has recently been shown that the combination of these treatments alters the gene expression patterns in the ovary and endometrium, mainly dysregulating key metabolic pathways, which could lead to inadequate follicle and oocyte growth and preimplantation embryo developmental ability [14]. Although the quality of the surviving blastocysts after St-ALT plus superovulation treatment, in terms of total trophectoderm and inner cell mass cells, apoptosis rates, and cryotolerance [13], was similar to that observed in ALT-untreated, superovulated sows and in natural postweaning estrus sows, the treatment can influence not only oocyte maturation and fertilization but also surviving embryos at the molecular level. The aim of the present investigation was to establish the extent to which St-ALT treatment in combination with a standard superovulation protocol in weaned sows caused variations in the overall transcriptome of day 6 embryos.…”
Section: Introductionmentioning
confidence: 99%
“…A better knowledge of the immunological mechanism underlying the establishment and maintenance of pregnancy in pigs is essential for the design of strategies to improve their reproductive efficiency. This challenge is especially relevant in the context of porcine ET; a technology that can notably contribute to improve sanitary, productive and, ultimately, economic aspects of the pig commercial sector (Gonzalez‐Ramiro et al., 2021 ). In addition, other relevant biotechnologies, such as gene editing or cloning, are highly dependent on ET (Martinez, Martinez, et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%